A concise history of translation in Iran from antiquity to the present time. (2nd October 2017) - Karoubi, Behrouz
ABSTRACT: The history of the practice of translation in Iran dates back more than 2000 years. During all these years, translation has always played a prominent role in the process of intercultural communication between Iran and the rest of the world. The current article aims at presenting a concise account of major developments in the theory and practice of translation in Iran from antiquity to the modern time, focusing on important historical turning points, such as the Arab conquest of Iran, the Iranian Constitutional Revolution, and the Islamic Revolution of 1979, that have given rise to different translation movements in this country. The article then provides a detailed analysis of the practice and theory of translation in present Iran by addressing a whole host of issues, such as translation policy, censorship, translation industry, translation pedagogy, and so on.